Components of the type six secretion system are substrates of Francisella tularensis Schu S4 DsbA-like FipB protein. Issue 8 (16th November 2016) - Qin, Aiping; Zhang, Yan; Clark, Melinda E.; Moore, Emily A.; Rabideau, Meaghan M.; Moreau, G. Brett; Mann, Barbara J.
ABSTRACT: FipB, an essential virulence factor in the highly virulent Schu S4 strain of F. tularensis subsp. tularensis, shares sequence similarity with Disulfide Bond formation (Dsb) proteins, which can have oxidoreductase, isomerase, or chaperone activity. To further explore FipB's role in virulence potential substrates were identified by co-purification and 2D gel electrophoresis, followed by protein sequencing using mass spectrometry. A total of 119 potential substrates were identified. Proteins with predicted enzymatic activity were prevalent, and there were 19 proteins that had been previously identified as impacting virulence. Among the potential substrates were IglC, IglB, and PdpB, three components of the Francisella Type Six Secretion System (T6SS), which is also essential for virulence. T6SS are widespread in Gram-negative pathogens, but have not been reported to be dependent on Dsb-like proteins for assembly or function. The presented results suggest that FipB affects IglB and IglC substrates differently. In a fipB mutant there were differences in free sulfhydryl accessibility of IglC, but not IglB, when compared to wild-type bacteria. However, for both proteins FipB appears to act as a chaperone that facilitates proper folding and conformation. Understanding the role FipB plays the assembly and structure in this T6SS may reveal critical aspects of assembly that are common and novel among this widely distributed class of secretion systems.